Assessing urban sidewalk networks based on three constructs: a synthesis of pedestrian level of service literature. Issue 2 (3rd March 2020) - Nag, Dipanjan; Goswami, Arkopal Kishore; Gupta, Ankit; Sen, Joy
ABSTRACT: Pedestrian Level of Service (PLOS) models are widely used to assess walking facilities. These models have been in existence since the 1970s, wherein the process broadly consists of three steps, i.e. attribute selection, model calibration, and classification of model results into service-level categories, based on Measures of Effectiveness (MOEs). This paper reviews existing sidewalk PLOS studies based on their association with the three constructs of flow characteristics, built environment and users' perception, which in combination represents the entire walking environment spectrum, as has been indicated by existing researchers. Forty-seven PLOS studies, along with eight review papers, written by authors from the Americas, Europe, Asia and Australia, between the years of 1971 and 2019, are analysed in this review. The review finds that although 49% of the studies employed both qualitative and quantitative data for their respective methodologies, but none of them use all the three broad constructs in a combined fashion. Also, in selecting the attributes to be used for developing the PLOS, these studies have only referred to previous literature available at that point in time, and not employed any consistent and robust method in selecting context-specific attributes. When it came to the preferred analysis technique, 60% of the studies favoured the use of the regression technique while calibrating their model, whereas 22% used a points-based marking scheme. Finally, 89% of the studies manually classifies the PLOS model results to respective service levels (i.e. letter grades), as opposed to utilising a classification algorithm. In addition, this review could identify only one paper that describes a PLOS based on pedestrian route directness, which is a measure of pedestrian network connectivity. In view of these findings, the review paper suggests the need of a robust methodology in selection of attributes and the use of innovative modelling techniques, both of which could allow the utilisation of all three constructs. Also, such advanced modelling techniques could bypass the need for categorising service levels manually. Finally, the study advocates the use of network connectivity measures in developing sidewalk PLOS, as it is an important part of the built environment.